Encyclia lopezii (Orchidaceae, Laeliinae) a new species from Venezuela - Leopardi, Carlos; Carnevali, Germán; Romero-González, Gustavo A. (Phytotaxa, 2012)
A new species from Venezuela, Encyclia lopezii, is proposed. Encyclia lopezii is similar to E. cordigera and both species share the large flowers, the broad, suborbicular-subquadrate labellum central lobe, and the obovate to spathulate petals. Encyclia lopezii is, however, different from E. cordigera in several characters, including the subapically winged column with straight margins, the verrucose pedicellate ovary, and the fact that the apices of the lateral lobes of the lip do not overlap on top of the column at anthesis. The new species is fully illustrated and described. Encyclia cordigera and an Andean form of E. diurna are also documented with illustrations and discussed in the context of the relationships of the new species here proposed. A conservation assessment of Encyclia lopezii is provided following the IUCN criteria.